Feline Vector-Borne Diseases and Their Possible Association with Hematological Abnormalities in Cats from Midwestern Brazil - Stephani Félix Carvalho; Gracielle Teles Pádua; Warley Vieira de Freitas Paula; Mariana Avelar Tavares; Lucianne Cardoso Neves; Brenda Gomes Pereira; Rayane Almeida Santos; Gabriel Cândido dos Santos; Ennya Rafaella Neves Cardoso; Andriele Ferreira Qualhato; Raphaela Bueno Mendes Bittencourt; Nicolas Jalowitzki de Lima; et al. (Microorganisms)
Among the parasitic and infectious diseases affecting cats, those caused by vector-borne pathogens deserve attention due to their ability to cause nonspecific clinical signs and clinicopathological abnormalities. We studied the presence of Cytauxzoon spp., Ehrlichia spp., and Mycoplasma spp. in blood samples from 135 cats referred to the veterinary teaching hospital of the Federal University of Goiás in midwestern Brazil. We also investigated co-infections with Feline Immunodeficiency Virus (FIV) and Feline Leukemia Virus (FeLV) as well as the correlation between Mycoplasma spp. infection and cat variables, including age, sex, breed, and complete blood count abnormalities. Upon PCR testing, 20.7% (28/135) of samples were positive for Mycoplasma spp., 1.5% (2/135) for Cytauxzoon spp., and none for Ehrlichia spp. Co-infections with Mycoplasma spp. and Cytauxzoon spp. were detected in the two cats with the latter infection. Mycoplasma spp. infection was statistically associated with the simultaneous presence of thrombocytopenia and leukocytosis. This study confirms a high frequence of Mycoplasma spp. infection, with both M. haemofelis and ‘Candidatus Mycoplasma haemominutum’ circulating in this cat population. The clinical significance of Mycoplasma spp. infection in cats should be further explored and this infection should eventually be included in the differential diagnosis of thrombocytopenia and leukocytosis in otherwise apparently healthy cats.